AGAMA TRADISI DAN WACANA SPRITUALITAS ABAD 21; KEARIFAN MEWUJUDKAN RUANG PUBLIK YANG DIDOMINASI OLEH MODERASI - Nasution, Marlian Arif (UIN Sumatera Utara Medan, 2023)
This article comes as a response to the tragedy of intolerance in the name of religion and spiritual discourse of the 21st century, the focus of his study is to answer the problem of how to realize a public space dominated by moderation of all components of life. The data used in this article is sourced from library research and applies an interdisciplinary approach. The research findings are; Many religious researchers argue, religion will experience extinction in modern society, what happens is the repositioning of the epistemological building of religious traditions through spiritual discourse based on empirical research, namely; 3P + 2S (Personal Relationship, Psitivity, Passion + Sense of Progress, Spritual Blue Diamons). This spiritual discourse does not intend to replace religion. The aim is to encourage a more harmonious public life, without eliminating the role of religion for life, preserving relevant elements in religion, discarding obsolete religious ways. Meanwhile, efforts to realize public spaces dominated by moderation are; Every individual must understand the basic concepts of religion and religious relations, understand the principles of religion, humanity, and togetherness, revive ukhuwah Islamiyah for social networks, as well as actualize spiritual wisdom and religious rationality.